2008
DOI: 10.1172/jci33946
|View full text |Cite
|
Sign up to set email alerts
|

Making a bad thing worse: adverse effects of stress on drug addiction

Abstract: Sustained exposure to various psychological stressors can exacerbate neuropsychiatric disorders, including drug addiction. Addiction is a chronic brain disease in which individuals cannot control their need for drugs, despite negative health and social consequences. The brains of addicted individuals are altered and respond very differently to stress than those of individuals who are not addicted. In this Review, we highlight some of the common effects of stress and drugs of abuse throughout the addiction cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 94 publications
3
77
0
1
Order By: Relevance
“…First, NPSR mRNA is abundantly expressed in brain regions (ie, amygdala, hippocampus, and lateral hypothalamus) that are known to play a significant role in the regulation of alcohol drinking and reinstatement of alcohol seeking (Heilig and Koob, 2007;Le and Shaham, 2002). Second, the arousing effects of NPS together with its activation of the HPA axis system may establish a condition resembling the pathophysiological state associated with excessive alcohol use or that preceding relapse (Adinoff et al, 2005;Cleck and Blendy, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…First, NPSR mRNA is abundantly expressed in brain regions (ie, amygdala, hippocampus, and lateral hypothalamus) that are known to play a significant role in the regulation of alcohol drinking and reinstatement of alcohol seeking (Heilig and Koob, 2007;Le and Shaham, 2002). Second, the arousing effects of NPS together with its activation of the HPA axis system may establish a condition resembling the pathophysiological state associated with excessive alcohol use or that preceding relapse (Adinoff et al, 2005;Cleck and Blendy, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Like stressors, morphine withdrawal activates the HPA axis in rats, which results in neuronal activation of stress-related neurosecretory neurons in the parvocellular division of the hypothalamic paraventricular nucleus (PVN), an increase in CRF transcription, and boost of adrenocorticotropin and corticosterone secretion (Laorden et al, 2002b;Nú ñ ez et al, 2007a;Cleck and Blendy, 2008). Enhanced responsiveness of HPA axis after morphine withdrawal has been associated with activation of noradrenergic neurons in the nucleus tractus solitarius (NTS)-A 2 that project to the hypothalamic PVN (Laorden et al, 2000b(Laorden et al, , 2002b.…”
mentioning
confidence: 99%
“…Several areas of the central nervous system are involved in the integration between behavioral and cardiovascular response associated with morphine withdrawal. Thus, naloxoneinduced morphine withdrawal produces adaptive changes in the heart (Rabadán et al, 1997;Peart and Gross, 2006;Almela et al, 2008) and activation of the HPA axis (Laorden et al, 2002;Cleck and Blendy, 2008;Nú ñ ez et al, 2009). The present findings demonstrated that naloxone administration to morphine-dependent rats significantly elevated plasma adrenocorticotropin and corticosterone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In rats activation of the HPA axis has been observed with agonists of the three types of opioid receptors when given peripherally and centrally (Haracz et al, 1981;Pfeiffer et al, 1985;Iyengar et al, 1987), and it has been described that, like stressors, morphine withdrawal increases heart rate (Almela et al, 2011) and activates the HPA axis in rats, which results in the neuronal activation of stress-related neurosecretory neurons in the parvocellular neurons of the hypothalamic paraventricular nucleus (PVN), an increase in CRF transcription, and boosts of adrenocorticotropin and corticosterone secretion (Laorden et al, 2002;Cleck and Blendy, 2008;Nú ñ ez et al, 2009). Furthermore, the profound cellular stress induced by chronic morphine treatment and withdrawal is also evidenced by the overexpression of heat shock proteins (Hsps) (Kas, 1987;Sharma and Ali, 2006).…”
Section: Introductionmentioning
confidence: 99%